1982
DOI: 10.1002/app.1982.070270111
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the effect of titanate coupling agent on the performance of polypropylene–calcium carbonate composite

Abstract: SynopsisComposites of polypropylene-CaC03 coated with isopropoxy triisostearoyl titanate have been prepared on Buss KO-Kneader. These composites have been evaluated for mechanical properties, melt index, dispersion, and adhesion of polymer to filler using the scanning electron microscope. Calcium carbonate being a platelike substance with low aspect ratio results in com~osites having inferior tensile properties but superior impact characteristics. Uniform dispersion of filler in the composite and long alkyl ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…It has been observed, in studies of the solid-state properties of i-PP/CaSiO 3 /LICA 38 composites, that LICA 38 smoothens the particle surfaces, and its long alkyl moiety exhibits a plasticizing/lubricating type of function 15 similar to that noted in studies of other composites. 6,10,32 It appears that this plasticizing/lubricating function is also operative under the melt flow conditions that decrease the app values to a certain extent.…”
Section: Apparent Melt Viscosity ( App )mentioning
confidence: 94%
“…It has been observed, in studies of the solid-state properties of i-PP/CaSiO 3 /LICA 38 composites, that LICA 38 smoothens the particle surfaces, and its long alkyl moiety exhibits a plasticizing/lubricating type of function 15 similar to that noted in studies of other composites. 6,10,32 It appears that this plasticizing/lubricating function is also operative under the melt flow conditions that decrease the app values to a certain extent.…”
Section: Apparent Melt Viscosity ( App )mentioning
confidence: 94%
“…Silane and titanate types of coupling agents have been gaining importance in recent time, and many claims and counterclaims have been made about its efficacy. Sharma et al 11 in their article on the effect of a titanate coupling agent on the performance of CaCO 3 -filled PP showed that upon the treatment of the filler with an isopropoxy triisostearoyl titanate coupling agent, a 20% improvement in the impact strength was recorded, whereas the elongation at break of the composite was slightly less than that of virgin PP. They also claimed that this increase in the impact strength was not as evident as reported by Han et al, 12 who also worked on PP/CaCO 3 systems previously, even though the fillers were also treated with titanate coupling agents.…”
Section: Introductionmentioning
confidence: 95%
“…As nCaCO 3 does not exhibit good adhesion and dispersion in a matrix of PP, various surface treatments have been applied. 4,5 Much research has been reported about the surface modification of nCaCO 3 6,7 and the effects of modified nCaCO 3 on the properties of PP. 8 The most widely used methods of surface modification are surface grafting and coupling, such as the grafting of unsaturated carboxylic acids and the coupling of titanates, aluminates, phosphates, and zirconates.…”
Section: Introductionmentioning
confidence: 99%